Salt-inducible kinase inhibition promotes the adipocyte thermogenic program and adipose tissue browning - Fubiao Shi; Flaviane de Fatima Silva; Dianxin Liu; Hari U. Patel; Jonathan Xu; Wei Zhang; Clara Türk; Marcus Krüger; Sheila Collins (Elsevier, 2023)
Objective: Norepinephrine stimulates the adipose tissue thermogenic program through a β-adrenergic receptor (βAR)-cyclic adenosine monophosphate (cAMP)-protein kinase A (PKA) signaling cascade. We discovered that a noncanonical activation of the mechanistic target of rapamycin complex 1 (mTORC1) by PKA is required for the βAR-stimulation of adipose tissue browning. However, the downstream events triggered by PKA-phosphorylated mTORC1 activation that drive this thermogenic response are not well understood. Methods: We used a proteomic approach of Stable Isotope Labeling by/with Amino acids in Cell culture (SILAC) to characterize the global protein phosphorylation profile in brown adipocytes treated with the βAR agonist. We identified salt-inducible kinase 3 (SIK3) as a candidate mTORC1 substrate and further tested the effect of SIK3 deficiency or SIK inhibition on the thermogenic gene expression program in brown adipocytes and in mouse adipose tissue. Results: SIK3 interacts with RAPTOR, the defining component of the mTORC1 complex, and is phosphorylated at Ser884 in a rapamycin-sensitive manner. Pharmacological SIK inhibition by a pan-SIK inhibitor (HG-9-91-01) in brown adipocytes increases basal Ucp1 gene expression and restores its expression upon blockade of either mTORC1 or PKA. Short-hairpin RNA (shRNA) knockdown of Sik3 augments, while overexpression of SIK3 suppresses, Ucp1 gene expression in brown adipocytes. The regulatory PKA phosphorylation domain of SIK3 is essential for its inhibition. CRISPR-mediated Sik3 deletion in brown adipocytes increases type IIa histone deacetylase (HDAC) activity and enhances the expression of genes involved in thermogenesis such as Ucp1, Pgc1α, and mitochondrial OXPHOS complex protein. We further show that HDAC4 interacts with PGC1α after βAR stimulation and reduces lysine acetylation in PGC1α. Finally, a SIK inhibitor well-tolerated in vivo (YKL-05-099) can stimulate the expression of thermogenesis-related genes and browning of mouse subcutaneous adipose tissue. Conclusions: Taken together, our data reveal that SIK3, with the possible contribution of other SIKs, functions as a phosphorylation switch for β-adrenergic activation to drive the adipose tissue thermogenic program and indicates that more work to understand the role of the SIKs is warranted. Our findings also suggest that maneuvers targeting SIKs could be beneficial for obesity and related cardiometabolic disease.